2018
DOI: 10.19082/6571
|View full text |Cite
|
Sign up to set email alerts
|

Nursing managers attitude toward spirituality and spiritual care in Khorasan Razavi Province hospitals in 2016

Abstract: Background and aimSpiritual care is an important part of nursing practice that seems to provide comprehensive care to patients. Nursing manager’s attention to the spiritual dimension is one of the most important aspects affecting human health. Therefore, the aim of this study was to determine nursing managers’ attitude to spirituality and spiritual care in hospitals in Khorasan Razavi Province in 2016.MethodsIn this cross-sectional study, 110 management nurses (8 matrons, 37 supervisors and 65 head nurses) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
12
0
1
Order By: Relevance
“…The anonymity of the participants was assured by gathering a certain number of demographic variables, so only those that are necessary for a suitable description of the sample and were in previous studies (Kaddourah, et al, 2018;Kavosi, et al, 2018) identified as possible influencing factors on attitudes towards spirituality and spiritual care. We calculated descriptive statistics (frequency, mean value, standard deviation) and used statistical tests (ANOVA, t-test).…”
Section: Description Of the Research Procedures And Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The anonymity of the participants was assured by gathering a certain number of demographic variables, so only those that are necessary for a suitable description of the sample and were in previous studies (Kaddourah, et al, 2018;Kavosi, et al, 2018) identified as possible influencing factors on attitudes towards spirituality and spiritual care. We calculated descriptive statistics (frequency, mean value, standard deviation) and used statistical tests (ANOVA, t-test).…”
Section: Description Of the Research Procedures And Data Analysismentioning
confidence: 99%
“…Anonimnost udeležencev smo zagotovili z zbiranjem omejenega števila demografskih spremenljivk, torej le tistih, ki so potrebne za zadosten opis vzorca in preverjanje njihove vloge v stališčih do duhovnosti in duhovne oskrbe znotraj nekaterih sodobnejših raziskav (Kaddourah, et al, 2018;Kavosi, et al, 2018). Izračunali smo opisne statistike (frekvenca, povprečna vrednost, standardni odklon) in uporabili statistične teste (ANOVA, t-test).…”
Section: Opis Poteka Raziskave In Obdelave Podatkovunclassified
“…23). Recent studies on spirituality suggest a great deal of benefits in a wide array of subjects, including health assistance and nursing (Kavosi et al, 2018;Kaddourah et al, 2018;Lorenzo, 2018), psychological treatment of various ailments (Jyothi and Sumesh, 2018;Oxhandler, et al 2018), impacts on work environments (Walia and Nishtha, 2018;Nair and Sivakumar, 2018) and many other areas that are primarily concerned with overall individual wellbeing (Czekóová et al, 2018).…”
Section: Introduction 1introduction To Spiritualitymentioning
confidence: 99%
“…Eight different countries were identified from the 14 documents to be jointly evaluated (Table 1). The country with the highest scientific output in this context is Brazil with 8 documents (57%), (7,9,(16)(17)(18)(19)(20)(21)(22) USA, (23) Australia, (24) Iran, (25) Ghana, (8) Colombia, (26) and India (27) with one study each per country. The purpose of this research study was to explore the various factors that influence the utilization of this nursing process.…”
Section: Resultsmentioning
confidence: 99%